PENGARUH REFERENCE GROUP, LIFESTYLE DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA FLAMBOYAN STREET FOOD MANADO) - Raturandang, Ireyne Filania; Lumanauw, Bode; Wenas, Rudy S. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This research adopts a quantitative approach, with data collected through questionnaires distributed to 100 respondents who are consumers in the area. The data were analyzed using multiple linear regression, along with validity and reliability tests, classical assumption tests, t-test, F-test, and coefficient of determination analysis. The results show that all three independent variables simultaneously have a significant influence on purchase decisions. Partially, lifestyle has the most dominant and significant positive effect, followed by social media marketing and reference group. This research contributes theoretically to the field of marketing management and offers practical recommendations for MSME business actors in designing marketing strategies aligned with modern consumer characteristics.